The Congress of Chuquisaca of 1837 and the seams of the state-building process of Bolivia - Colàs, Pol (Revista Complutense de Historia de América, 2023)
After independence, the Latin American state-building process lived through evident moments of tension that covered the totality of the geographical region. A profound study of these events allows for a detailed knowledge of the noteworthy number of actors, interests, consensuses, and internal struggles that constituted the motor of stateization, which discards historiographical conceptions that attribute exclusive primacy to the executive or to “caudillist” decisions within the power structure. Focusing on the correspondence collection of Bolivian president Andrés de Santa Cruz, the study centers on the analysis of the Congress of Chuquisaca of 1837, where an alliance between the citizens, the locality and the legislative power was postulated in favor of a purely Bolivian national project that was contrary to that of the executive, who had interests in La Paz, and which pretended to consolidate the expansionist Peruvian-Bolivian Confederation. This pact ended up initiating a revolutionary cycle of public opposition to the government around the Bolivian capital which, with its ups and downs, finally prevailed in 1839, bringing about the end of the confederate adventure and the administration of Santa Cruz. With this focus, the article aims to reveal the depth of the power struggles between the legislature and the executive, and the strength of the locality and of the autonomous citizens’ movements in their struggle for hegemony, as well as the direction that this conflict gave to the state-building process that covered it. All this, being a local event, in an undeniable relationship with the rest of Latin America that can provide elements for the analysis of the general process, proposing comparisons with analogous cases in the region.